Visualization of hepatitis B virus entry: novel tools and approaches to directly follow virus entry into hepatocytes - Zhang, Zhenfeng; Zehnder, Benno; Damrau, Christine; Urban, Stephan (FEBS letters, 2016)
Hepatitis B virus (HBV) is a widespread human pathogen, responsible for chronic infections of ca. 240 million people worldwide. Until recently, the entry pathway of HBV into hepatocytes was only partially understood. The identification of human sodium taurocholate cotransporting polypeptide (NTCP) as a bona fide receptor of HBV has provided us with new tools to investigate this pathway in more details. Combined with advances in virus visualization techniques, approaches to directly visualize HBV cell attachment, NTCP interaction, virion internalization and intracellular transport are now becoming feasible. This review summarizes our current understanding of how HBV specifically enters hepatocytes, and describes possible visualization strategies applicable for a deeper understanding of the underlying cell biological processes.